2021
DOI: 10.1186/s12916-021-02163-6
|View full text |Cite
|
Sign up to set email alerts
|

5mC regulator-mediated molecular subtypes depict the hallmarks of the tumor microenvironment and guide precision medicine in bladder cancer

Abstract: Background Depicting the heterogeneity and functional characteristics of the tumor microenvironment (TME) is necessary to achieve precision medicine for bladder cancer (BLCA). Although classical molecular subtypes effectively reflect TME heterogeneity and characteristics, their clinical application is limited by several issues. Methods In this study, we integrated the Xiangya cohort and multiple external BLCA cohorts to develop a novel 5-methylcyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 72 publications
(74 reference statements)
0
59
0
Order By: Relevance
“…In our research, we found that most m7G regulators were favorable factors for KIRC, whereas NUDT11, NUDT10, NSUN2, WDR4, METTL1, LSM1, and EIF4A1 were risk factors. These genes all play an oncogenic role in cancer ( Chen Z et al, 2021 ; Grisanzio et al, 2012 ; Hu J et al, 2021 ; Little et al, 2016 ; Wang et al, 2021 ; Xia et al, 2021 ; Ying et al, 2021 ; Zhao et al, 2021 ). Pan-cancer analysis showed that WDR4 and METTL1 were closely related to cancer immune infiltration and were immunotherapy targets in patients, and the high expression of KIRC was associated with poor prognosis of patients ( Gao et al, 2022 ; Zeng et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our research, we found that most m7G regulators were favorable factors for KIRC, whereas NUDT11, NUDT10, NSUN2, WDR4, METTL1, LSM1, and EIF4A1 were risk factors. These genes all play an oncogenic role in cancer ( Chen Z et al, 2021 ; Grisanzio et al, 2012 ; Hu J et al, 2021 ; Little et al, 2016 ; Wang et al, 2021 ; Xia et al, 2021 ; Ying et al, 2021 ; Zhao et al, 2021 ). Pan-cancer analysis showed that WDR4 and METTL1 were closely related to cancer immune infiltration and were immunotherapy targets in patients, and the high expression of KIRC was associated with poor prognosis of patients ( Gao et al, 2022 ; Zeng et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…METTL1 and WDR4 are highly expressed in a variety of tumors, such as liver cancer ( Chen D et al, 2021 ), intrahepatic cholangiocarcinoma ( Dai S et al, 2021 ), and lung cancer ( Ma et al, 2021 ), which is related to poor prognosis of patients. High expression of NSUN2 is associated with poor prognosis of gastric cancer ( Hu J et al, 2021 ) and esophageal squamous cell carcinoma ( Su et al, 2021 ). NUDT10 is a reliable prognostic marker of gastric cancer ( Chen Z et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent to previous studies showing that the patterns of m 6 A regulators are associated with immune evasion and prognosis in other cancer types. Zu’s group evaluated the expression landscape of regulators for 5-methylcytosine (5mC), an epigenetic modification [ 9 ]. They identified two clusters of 5mC regulators that were correlated with the classical molecular subtypes and prognosis of bladder cancer.…”
Section: Targeted Therapy: An Evolving Paradigmmentioning
confidence: 99%
“…In addition, Gao et al ( Gao et al, 2019 ) found that high expression of NSUN2 could promote the proliferation and tumorigenesis of gallbladder carcinoma cells both in vitro and in vivo by closely cooperating with ribosomal protein L6. Recently, the role of m5C modification in cancers, including lung cancer, colon carcinoma, bladder cancer, and thyroid carcinoma, has been explored ( Pan et al, 2021a ; Pan et al, 2021b ; Chen et al, 2021 ; Gao et al, 2021 ; Geng et al, 2021 ; Gu et al, 2021 ; Hu et al, 2021 ; Li et al, 2021 ; Liu et al, 2021 ; Xu et al, 2021 ). In addition, He et al ( He et al, 2020a ) built a gene signature including 2 m5C regulators and found that it could effectively predict the prognosis of HCC.…”
Section: Introductionmentioning
confidence: 99%